(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article examines the importance of corporate culture as a strategic factor in the system of human resource management. The main theoretical approaches to the definition and typology of corporate culture (the models of E. Shine, C. Handy, Cameron and Quinn) are analyzed, and the relationship between the type of organizational culture and the effectiveness of HR processes is revealed Staff.